The Impact of the SARS-CoV-2 Pandemic on Bone Marrow Transplants in Brazil - Silva, Sacha Krolow e; Seki, Jéssica Manami; Blume, Helena Angelica; Henrique, Matheus Vinícius; Fructos, Marcela Silva; Marchese, Maria Eduarda Meirelles; Vaniel, Júlia de Azambuja; Silva, Thais Matos; Schuh, Ketlin Laufer; Pereira, Luanna Carla Brandão; Paim, Julia Stela Xavier; Freitas, Eduarda Correa; et al. (Brazilian Journal of Transplantation, 2026)
Introduction: Bone marrow transplantation (BMT) is an established therapy for the treatment of various health conditions. In Brazil, procedures are registered by the Brazilian Association of Organ Transplants (ABTO) and the Hospital Information System of the National Health System (SIH/SUS). The COVID-19 pandemic has forced health systems to adapt to the increased risk of death. Objectives: To evaluate the landscape of BMT in Brazil from 2018 to 2024, comparing the pre-pandemic, pandemic, and post-pandemic periods in terms of frequency, type of transplant, registration, and regional distribution. Methods: A retrospective descriptive study using data on BMTs performed from January 2018 to June 2024, from the databases of the SIH/SUS and the ABTO, which were subsequently analyzed in an R environment. Results: A total of 21,164 BMTs were recorded by ABTO (61% autologous) and 5,841 by SIH/SUS (predominantly allogeneic). A reduction in procedures was observed during the pandemic, followed by a recovery in the post-pandemic period in both databases (ABTO: +32.6% vs. pandemic period; SIH/SUS: +29.1%). ABTO maintained a predominance of autologous transplants (≈ 58-61%), while SIH/SUS showed a consistent predominance of allogeneic transplants (≈ 73-75%), mainly from related donors. There was a strong regional concentration in the Southeast, especially in São Paulo, followed by the South, Northeast, Midwest, and North. The analyses did not show statistically significant differences between regions but showed a post-pandemic growth trend. Regional heterogeneity was observed in terms of the type of transplant and marked inequality in the distribution of transplant centers, with a worse center/patient ratio in the North and Midwest regions. Despite the numerical differences, the databases showed convergent temporal and regional patterns. Conclusion: From 2018 to 2024, BMT procedures in Brazil were significantly impacted by the pandemic, with subsequent recovery in both databases. The findings highlight structural inequalities in access to transplantation and reinforce the need for greater integration and standardization of information systems, as well as the expansion of infrastructure in less-served regions.